Miri City Council “5s Practice” / Valarie Aren Mering - Mering, Valarie Aren (University Technology MARA Sarawak, 2013)
Miri City Council which under Ministry of Environment and Public Health (KASKA) is the main organization in managing the development of Miri city. Its jurisdiction area is about 997.43 sq. km. The responsibility of council has become more important when Miri was recognized as a city on 20th May 2005. The main function of theMiri City Council is providing public services as well as managing events and affairs of Miri City. Services provided by Miri City Council includes rubbish collecting, providing street lighting, maintenance of roads and drains, managing the disposal and conservancy system, collecting of assessment rates, bills and others which are under the authority of theMiri City Council. In term of achievement, Miri City Council won the award at the national level in beautiful landscape category competition. Miri City attracts visitors from all over the world. This brings income to prosper the economy of Miri.